Intermediation in Search Markets - Thomas Gehrig (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
In markets, in which exchange requires costly search for trading partners, intermediaries can help to reduce the trading frictions. This intuition is modelled in a framework with heterogeneous agents, who have the chocie between intermediated exchange and search accompanied by some bargaining procedure. The equilibria of such a game are characterized. In the case of a monopolistic intermediary the tradeoff between the bid-ask spread and the costs of delay during private search determine the intermediary's clientele. In equilibrium the monopolist charges a positive spread. Traders with large gains from trade prefer to deal with him, whereas traders with relatively low gains from trade engage in search. In case of competition among intermediaries the classical Bertrand result obtains and bid and ask prices converge to the (unique) Walrasian equilibrium price. Thus in the confines of the model the Walrasian auctioneer of the market under consideration can be replaced by competing intermediaries. In addition a multiplicity of subgame perfect Nash edquilibria emphasizes the coordination problemms inherent in models of intermediation.
Keywords: C78; D83; L12; 330; intermediation; incomplete information; price competition; transaction costs